Imprisonment of children with their mothers : a comparative analysis - Khoza, Zanele Cadina (My University, 2024)
Refer to document
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2025
Keywords: Improsonment; Children with their mothers; Imprisonment -- South Africa; Prisons; Correctional institutions; Women prisoners; Children of women prisoners